Structure Analysis = Cơ học kết cấu - Bộ môn Sức bền kết cấu (Trường Đại học Thuỷ Lợi, 2020)
Contents: Chapter 1: Introduction; Chapter 2: Design Loads; Chapter 3: Statics of Structures-Reactions; Chapter 4: Trusses; Chapter 5: Beams and Frames; Chapter 8: Live Load Forces: Influence Lines for Determinate Structures; Chapter 9: Deflections of Beams and Frames; Chapter 10: Work-Energy Methods for Computing Reflections; Chapter 11: Analysis of Indeterminate Structures by The Flexibility Method; Chapter 12: Analysis of Indeterminate Beams and Frames by the Slope-Deflection Method